Focus Groups in Hospitality Research Why are they not used in Jordan? - Mousa Masadeh; Mukhles Al-Ababneh; Samer Al-Sabi; Bashar Maaiah (European Scientific Journal, ESJ, 2016)
The purpose of this study is to identify the reasons for the lack of focus groups in Jordan by conducting a focus group with twenty four Academics from Jordanian Universities. Focus groups are commonly used for academic purposes and taught at colleges and universities. The outcome of focus groups for marketing, especially in the tourism industry, is a beneficial learning tool. Focus groups, however, are rarely used for a number of reasons. This research tool is foreign to university students, and unless they study abroad, they are not exposed to a wide range of research and education tools. There are barriers that exist with focus groups. These barriers include: government and educational funding, cultural limitations, personal expectations, teaching materials and resources. Following this research, the recommendations are to have focus groups implemented in Jordanian school systems and to conduct focus group training sessions, encourage students to use them as a research tool and explain the link between focus groups and the hospitality industry. By limiting curriculums in Jordanian education systems, students will not have the proper knowledge or skills once they graduate to compete with markets outside of Jordan. Recommendations are discussed based on the author’s research findings.